Colon cancer in rapidly developing countries: review of the lifestyle, dietary, consanguinity and hereditary risk factors - Abdulbari Bener (Frontiers Media S.A., 2011)
Colon cancer rates are rising dramatically in once low incidence nations. These nations are undergoing rapid economic development and are known as "nations in transition" (NIT). This review identifies some of the most common etiological risk factors of colon cancer in these nations and evaluates the existing epidemiological evidence. The main risk factors which were found to be prevalent in NIT include: lifestyle factors such as physical inactivity, obesity and abdominal adiposity, alcohol consumption and cigarette smoking; dietary factors such as fatty food and red meat consumption. Protective factors included white meat and fiber consumption. Several studies found to have significantly higher rates of colon cancer among the young population (<40 years old). There appears to be a quantitative and qualitative increase in risk to relatives of patients diagnosed at a young age compared with those diagnosed later in life, at least part of which is likely to be the result of a hereditary susceptibility. Close relatives of patients with colon cancer are at an increased risk of developing a colon cancer. Close relatives of early onset cases warrant more intensive endoscopic screening and at an earlier age than relatives of patients diagnosed at older ages. Furthermore, these suggest the existence of genetic predispositions in these nations which need to be investigated further and have implications for screening programs. In conclusion, public health awareness campaigns promoting prevention of modifiable risk factors and screening initiatives with guidelines suited to the age-specific incidence rates of NIT are needed very urgently.